2021
DOI: 10.1002/onco.13754
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Cetuximab-Based Salvage Chemotherapy After Checkpoint Inhibitors in Head and Neck Cancer

Abstract: Background. There are still few data on the activity and safety of cetuximab-based salvage chemotherapy after immunotherapy (SCAI) in patients with squamous cell cancer of the head and neck (SCCHN). Materials and Methods. Retrospective study of patients with SCCHN who received cetuximab-based SCAI after PD1 or PDL1 (PD(L)1) inhibitors. Overall response rate (ORR) and disease control rate (DCR) with SCAI and with last chemotherapy before immunotherapy (LCBI) by RECIST 1.1, percentage change from baseline in tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
2
19
0
1
Order By: Relevance
“…Regarding salvage chemotherapy following nivolumab therapy, we mainly performed paclitaxel and cetuximab therapy, and our clinical outcomes, including 41% ORR, were comparable to those of previous studies [29][30][31] . As mentioned above, since the efficacy of cetuximab and other chemotherapies following ICI has been reported, relatively early changes in treatment modalities might be acceptable.…”
Section: Discussionsupporting
confidence: 77%
“…Regarding salvage chemotherapy following nivolumab therapy, we mainly performed paclitaxel and cetuximab therapy, and our clinical outcomes, including 41% ORR, were comparable to those of previous studies [29][30][31] . As mentioned above, since the efficacy of cetuximab and other chemotherapies following ICI has been reported, relatively early changes in treatment modalities might be acceptable.…”
Section: Discussionsupporting
confidence: 77%
“…Regarding salvage chemotherapy following nivolumab therapy, we mainly performed paclitaxel and cetuximab therapy, and our clinical outcomes, including 41% ORR, were comparable to those of previous studies [25][26][27] . As mentioned above, since the e cacy of cetuximab and other chemotherapies following ICI has been reported, relatively early changes in treatment modalities might be acceptable.…”
Section: Discussionsupporting
confidence: 75%
“…The combination of ICI therapy and chemotherapy has a synergistic effect, and recent studies have confirmed its efficacy [17]. Chemotherapy has also been shown to be more effective in R/M HNSCC after progression following ICI therapy [8,9,18]. This emphasizes the importance of not only the use of ICI and chemotherapy in combination but also the treatment sequence of ICI and chemotherapy.…”
Section: Discussionmentioning
confidence: 94%
“…The efficacy of cetuximab-containing regimens after the use of ICIs in R/M HNSCC has been recently reported, and this may be the result of a synergistic effect of ICIs and cetuximab, as described above. However, multiple regimens including cetuximab have been evaluated in these reports, and individual regimens were not considered [18,23]. This is the first report to describe the efficacy and safety of a regimen limited to Cmab + PTX after progression following ICI therapy, which has important implications for the optimization of the treatment sequence for R/M HNSCC.…”
Section: Discussionmentioning
confidence: 99%